THE EXPRESSION OF LINGUISTIC AND CULTURAL FEATURES IN THE NAMES OF GAMES (Scientific journal of the Fergana State University, 2024)
In this article, a linguistic and cultural analysis of game names used in the field of preschool education is carried out, aspects related to nationality and folk values in names are considered. In the terminology of preschool education, play is considered the leading component, and five areas of development are formed exclusively through play. It is worth noting that the names of the games were interpreted in linguoculture as realities. Titles of games created using repetition serum are a fabrication. O. Safarov's book “Uzbek folk children's games” contains a number of games that are repeated